Application of ANNs and Dynamic Modeling for SMEs - Gunawan, Agus (Jurnal Administrasi Bisnis, 2012)
Indonesian SMEs Garment Manufacturers (ISGMs) has become the main contributorto Indonesiaâs Gross Domestic Product for the last ten years. At the same time, theState Minister for Cooperatives and SMEs received many reports on the discontinuedof the ISGMs. Currently, the ISGM managers have lack of management capabilities.This study focus on the use of artificial neural networks (ANNs) that is capableof interpreting the results of financial statements analysis (FSA). ANNs rules areencoded implicitly using an algorithm for automatic learning. Furthermore, the studyalso will investigate how to support the ISGMs by using pattern recognition in dy-namic modelling (DM). The combination of ANNs and DM may support the ISGMsin (1) analysing the firmâs performance, (2) interpreting the results of FSA, and (3)providing a simulation on what will happen if something occurred in the business.Keywords: financial statement analysis, ANNs, dynamic modelling, business,garment, SMEs